Digital Education and the Challenge of Personal Data Protection: An International Human Rights Law Perspective on State Obligations - Fausta, Vania Sokya; Prastyanti, Rina Arum (West Science Law and Human Rights, 2025)
There is currently a conflict between technological innovation and the preservation of privacy rights as a result of the increasing collection of students’ personal data caused by the digital transformation of education. Through the lens of international human rights law, this research seeks to understand states’ obligations to protect personal data in the context of digital education. This research examines three theoretical frameworks: the concept of International Due Dilligence, the interpretation of General Comment No. 16 of the UN Human Rights Committee, and Human Rights Protection Theory, using a normative legal methodology and doctrinal approach. The findings demonstrate significant weaknesses in traditional regulatory frameworks that prevent education data protection from incorporating a human rights perspective. In the context of digital education, this research shows that the state has three duties to uphold, defend and fulfill the right to data privacy. To assess the state’s compliance with its duties to prevent, address and remedy education data privacy violations, this research creates an evaluative model based on due diligence. The results are important for creating a human rights-based approach to regulating education data, providing a conceptual framework that strikes a balance between protecting fundamental rights and technological advancement, and increasing state accountability in digital education data governance.